2012
DOI: 10.1159/000338131
|View full text |Cite
|
Sign up to set email alerts
|

Biologic Therapies: Lessons from Multiple Sclerosis

Abstract: New evidence points to a possible association of multiple sclerosis (MS) with IBD. Tumour necrosis factor (TNF) is involved in the pathogenesis of MS. Paradoxically, administration of anti-TNF monoclonal antibodies to IBD patients has led to exacerbation of MS or triggered demyelination. TNF receptor 1 (TNFR1) mediates demyelination and TNFR2 mediates remyelination, suggesting that a more selective approach to TNF antagonism may be required for an anti-TNF strategy to be effective in MS. Conversely, interferon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 31 publications
(18 reference statements)
0
11
0
2
Order By: Relevance
“…(Mpofu et al , 2005) For example, all TNF blockers are highly effective in RA, but in Crohn disease there is a clear clinical benefit with infliximab but not etanercept (Targan et al , 1997; Sandborn et al , 2001) and the latter treatment exacerbates the pathology in multiple sclerosis. (Ghosh, 2012) A systematic characterization of Treg compartment in these patients has not been reported. Based on our data, we propose that the discrepancies in clinical outcomes with the TNF blockers may be partly due to differences in effectiveness of the drugs in improving the Treg compartment in different disease settings.…”
Section: Discussionmentioning
confidence: 98%
“…(Mpofu et al , 2005) For example, all TNF blockers are highly effective in RA, but in Crohn disease there is a clear clinical benefit with infliximab but not etanercept (Targan et al , 1997; Sandborn et al , 2001) and the latter treatment exacerbates the pathology in multiple sclerosis. (Ghosh, 2012) A systematic characterization of Treg compartment in these patients has not been reported. Based on our data, we propose that the discrepancies in clinical outcomes with the TNF blockers may be partly due to differences in effectiveness of the drugs in improving the Treg compartment in different disease settings.…”
Section: Discussionmentioning
confidence: 98%
“…The study comparing ustekinumab with etanercpet showed ustekinumab’s superiority to high-dose etanercept in managing of moderate-to-severe psoriasis (Griffiths et al 2010 ). However, a phase 2 clinical trials investigating efficacy of ustekinumab in MS displayed its inefficiency in reducing the number of enhancing lesions (Ghosh 2012 ; Scherl et al 2010 ). Despite encouraging results showing clinical benefits of IL-17 and IL-23 inhibition, recently published meta-analyses have underlined higher number of major adverse effects in comparison to placebo group and suggested that patients shall be monitored for these potential safety signals (Langley et al 2013 ; Spuls and Hooft 2012 ; Tzellos et al 2013 ).…”
Section: Th17 Lymphocytes and Their Pathways As Target For Therapy: Cmentioning
confidence: 99%
“…Despite the fact that these three different autoimmune diseases may share some underlying molecular mechanisms, there are clear and important differences. This is strikingly illustrated by TNF-␣ blockers, which have been successfully used to treat RA and Crohn's disease yet which exacerbate MS (69,70). Similarly, while susceptibility to MS, RA, and Crohn's disease is influenced by specific shared genetic polymorphisms, these polymorphisms may exert opposing effects (protective versus promoting) in one disease versus another (71).…”
Section: Conclusion and Potential Therapeutic Perspectivesmentioning
confidence: 99%